Sign, Signiﬁcation and Discourse - Baquião, Rubens César (Estudos Semióticos, 2011)
This paper intends to present the foundations of the greimasian semiotic theory and their new theoretical developments. We also introduce the linguistic concepts proposed by Saussure and Hjemslev and their development in semiotics of passions and in tensive semiotics. To demonstrate the application of the theory, a publicity text is analyzed. This text is organized around the ﬁgure of Jesus Christ. The notion of Christ’s spiritual power in western society enables the understanding and the integration of internal and external values in the concept of man. The divergent values represented by the self and the other – fundamental concepts in the development of human thinking – are integrated in the notion of compassion and Christian pain. In the idea of compassion of Christ, the self and the other share a place of equal values. In the contemporary representations of Christ, the sacred-Christian values are attenuated and there is a development of other values associated to the image of Christ. The ﬁgure of Christ is still recognizable, but the sacred pain is no longer central in contemporary discourse. The symbols and religious ﬁgures are fundamental elements in the area of culture and the changes in values related with these ﬁgures reﬂect (and refract) changes in the social organization.